Complex Circulation of Foot-and-Mouth Disease Virus in Cattle in Nigeria - Ularamu, Hussaini G.; Lefebvre, David J.; Haegeman, Andy; Wungak, Yiltawe S.; Ehizibolo, David O.; Lazarus, David D.; De Vleeschauwer, Annebel R.; De Clercq, Kris (Frontiers in Veterinary Science, 2020)
Nigeria is a large densely populated country in West Africa. Most of its livestock is raised in a pastoralist production system with typical long distance migration in search of water and feed. As the demand for animal products largely exceeds the domestic production, large numbers of livestock are imported from neighboring countries without sanitary restrictions. In Nigeria foot-and-mouth disease virus (FMDV) serotypes O, A and SAT2 are endemic since long time. Clinical outbreaks of FMD due to serotype SAT1 are described again since 2015, after an absence of more than 30 years. Historically, outbreaks of FMD due to serotypes O, A, SAT1 and SAT2 were each time associated with trade of cattle entering Nigeria from neighboring countries. In the present study tissue samples from 27 outbreaks of FMD were collected in Nigerian cattle from 2012 till 2017 in 6 different States and in the Federal Capital Territory. FMDV was isolated and serotyped and further characterized by VP1 sequencing and phylogenetic analysis to gain more knowledge on FMD virus circulation in Nigeria. Half of the outbreaks were characterized as FMDV topotype O/EA-3, while outbreaks with other serotypes and topotypes were – in descending order – less prevalent: A/Africa/G-IV, SAT1/X, SAT2/VII and O/WA. The high dynamics and omnipresence of FMD in Nigeria were illustrated in Plateau State where FMDV serotypes O, SAT1 and SAT2 were isolated during the course of the study, while at some point in the study outbreaks due to FMDV serotype A were observed in 3 remote States. The genetic and phylogenetic analysis suggests a mixed origin of FMD outbreaks. Some outbreaks seem to be caused by sustained local transmission of FMDV strains present in Nigeria since a number of years, while other outbreaks seem to be related to recent incursions with new FMDV strains. The role of African buffaloes in the etiology of FMD in Nigeria is unclear and sampling of wildlife is needed. The results of the present study suggest that systematic sample collection is essential to understand the complex concomitance of FMDV strains in Nigeria and essential to support the implementation of a vaccination-based control plan.